Legal fiction s studies of law and narrative in the discursive worlds of ancient Jewish sectarians and sages - Fraade, Steven D. (Supplements to the Journal for the Study of Judaism, 2011)
Ancient Jewish writings combine interpretive narratives of Israel's sacred history with legal prescriptions for a divinely ordered way of life. Two ancient Jewish societies have left us extensive textual corpora preserving interpenetrating legal and narrative interpretive teachings: the sectarian community of the Dead Sea Scrolls and the sage-disciple circles of the early Rabbis. This book comprises studies that explore specific aspects of the interplay of interpretative, narrative, and legal rhetoric with an eye to pedagogic function and social formation for each of these communities and for both of them in comparison. It addresses questions of how best to approach these writings for purposes of historical retrieval and reconstruction by recognizing the inseparability of literary-rhetorical textual analysis and a non-reductive historiography.